The Impact of Service Quality, Product Quality and Interest Rates on Customer Loyalty: The Mediating Role of Corporate Image (Case Study of Bank BRI's Kebon Jeruk Branch) - Pratiwi, Nori (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
This research aims to analyze the influence of service quality, product quality and interest rate levels on customer loyalty with the intervening variable of corporate image at BRI Kebon Jeruk branch office. This study uses a survey method with a sample of 95 people with the Simple Random Sampling technique. The data collection technique use saquestionnairethathas been tested for validity and reliability. The data analysis technique uses the SPSS 22.0 application by means of multiple linear regression analysis and path analysis tests . The results of the study provide the following conclusions: (1) service quality has a positive and significant effect on corporate image; (2) Product quality has a positive and significant effect on corporate image; (3) interest rates have a positive but not significant effect on corporate image; (4) service quality, product quality, and interest rates together have a positive and significant effect on corporate image; (5) service quality has a positive and significant effect on customer loyalty; (6) Product quality has a positive and significant effect on customer loyalty; (7) interest rates have a positive but not significant effect on member loyalty; (8) Perception, service quality have a simultaneous effect on customer loyalty; (9) Service quality, product quality, and interest rates have a simultaneous effect on customer loyalty through company image as an intervening variable.